Baseline Visual Acuity of Women with Diabetic Macular Edema is Worse than Men: A Case-Control Study - Abdullah Ozkaya (The Ophthalmology, 2017)
Purpose: To compare the baseline visual and anatomical parameters between the woman and men with diabetic macular edema (DME) who underwent intravitreal ranibizumab treatment. Materials and Methods: This was a retrospective case-control study. Treatment naïve DME patients who were newly diagnosed and completed a follow time of 12 months in our clinic were included. All the patients were prescribed to receive a loading dose of three consecutive monthly injections. Then the patients were followed monthly, and treated on a pro-re-nata treatment regimen. Primary outcome measures of this study was the baseline best corrected visual acuity (BCVA) and central retinal thickness (CRT) in the female and male patients at the baseline. Secondary outcome measures were the change in BCVA and CRT during the 12 months follow-up period. Results: Sixty-three eyes of 44 women, and 110 eyes of 76 men were included in the study. The mean baseline BCVA of the women was 0.72±0.44 (range 0.1-2.0) LogMAR, and the men was 0.49±0.31 (range 0.0-2.0) which was statistically significant between the two groups (p<0.0001). The mean baseline CRT of the women was 484±117 microns (range 312-759), and the men was 467±100 microns (range 320-704) (p=0.3). The mean visit number in women and men groups were 4.6±0.9 and 4.5±1.0, respectively (p=0.5). The mean injection number in women and men groups were 4.1±1.6 and 3.8±1.4, respectively (p=0.2). Conclusion: Our results revealed that there may be a significant difference in baseline BCVA between women and men with DME at the first admittance. Perhaps we should be more sensitive in periodic ophthalmology consultations of women with DME and warn the general health care practitioners, internal medicine specialists and endocrinologists in this regard.